Determination of Kaempferol in Rosa canina, Urtica dioica, Terebinthina chica and Portulace oleracea by HPLC-MS - Ozcan, Cemile; Yaman, Mehmet (Asian Journal of Chemistry, 2013)
The published studies on a positive association between the consumption of foods containing kaempferol and a reduced risk of developing several disorders such as cancer and cardiovascular diseases have increased the interest in the determination of this compound in foods. A high performance liquid chromatography-mass spectrometry (HPLC-MS) method was optimized for the determination of kaempferol in the different four plants and fruits matrices, rose hip (Rosa canina), nettle (Urtica dioica), terebinth (Terebinthina chica) and purslane (Portulace oleracea). Flow rate of mobile phase, fragmentor potential, injection volume and column temperature were found to be optimum values as 0.8 mL min-1, 140 V, 5 μL and 40 ºC, respectively. Limit of quantification (LOQ) were found to be 0.2 mg L-1. The optimized method was successfully applied to determination of kaempferol in the plant and fruits samples described above after their extraction with a mixture of HCl, methanol and ascorbic acid.